Ngayah: Communication Behaviour of Balinese Diaspora Jakarta - Gusti Ayu Jayanti Oka Utami; Dindin Dimyati (Fakultas Komunikasi, Sastra, dan Bahasa, 2020)
Pura Dalem Purnajati Tanjung Puri is one of Hindu temples located in Jakarta where Balinesepeople can observe and perform worship. However, in practice, Pura Dalem Purnajati TanjungPuri is also used as a place to observe traditional ceremonies such as Ngayah. Ngayah is a traditionconducted as a form of mutual assistance. The present study aimed to analyse the communicationbehaviour of Balinese diaspora in Jakarta for performing Ngayah. The present study usesqualitative method by conducting ethnography approach. Data was collected through observation,in-depth interview, and documentary study. The results show that Balinese diaspora in Jakartasimplified their tradition, including Ngayah tradition in Piodalan ceremony, where it can serve ascommunicative situation, communicative events, and communicative acts.Keywords: Balinese diaspora, Ngayah, culture, ethnography of communication